Antimicrobial properties of local vegetable amaranth (Amaranthus Gangeticus) - Mohammad Shariff, Nurul Nadia; Mohamed Rehan, Aisyah; Kamarudin, Kamarul Rahim (2008)
Amaranthus gangeticus have the potential to be used for medicinal purposes due to its nutrient composition. It is a leafy edible vegetable amaranth consumed worldwide. The aim of this study was to assess the antimicrobial activities of local edible Amaranthus gangeticus. The antibacterial activities of Amaranthus gangeticus and the type of bacteria sensitive to Amaranthus gangeticus were determined. The A. gangeticus leaves and stems were extracted by methanol and phosphate buffer saline (PBS) respectively and tested for its in vitro antimicrobial properties on Escherichia coli, Bacillus subtilis, Pseudomonas aeruginosa, Staphylococcus aureus, Candida albicans, Cryptococcus neoformans and Tricophyton mentagophytes. The paper disc diffusion method and agar well diffusion method were used to determine the inhibitory effects of both leaves and stem extracts of A. gangeticus on test microorganisms. The preliminary results of disc diffusion test revealed that the leaves extract of A. gangeticus produced a small zone of inhibition on P. aeruginosa, with the zone of inhibition of 5 mm, 7 mm and 8 mm for the concentration of 100 mg/ml, 200 mg/ml and 400 mg/ml respectively. Most of the test microorganisms are found to be resistant against extracts from A. gangeticus with only P. aeruginosa showed positive result. Further study needs to be performed to investigate the antimicrobial properties of A. gangeticus using agar well diffusion method for overall comparison of antimicrobial properties of both leaves and stems extracts of A. gangeticus.